Legal Protection of the Issuance of Birth Certificates of Children from Unregistered Marriages: An Analysis of Islamic Law and Indonesian Civil Law - Nur, Jabal; Lewa, Irfan; Maloko, M. Thahir (Parewa Saraq: Journal of Islamic Law and Fatwa Review, 2023)
The issuance of birth certificates for children born from unregistered marriages is a very important issue. In practice, there are still many places where children who will be born in an unregistered marriage relationship cause the absence of a valid certificate. The purpose of this study is to reveal legal protection, both from the aspect of legal status and legal consequences of the issuance of birth certificates of children from unregistered marriages. This paper is a qualitative empirical research with a comparative law approach. Data sources are obtained from interviews and literature studies. The results of the study found that children born from unregistered marriages have legal status as legitimate children of the father and mother because they have fulfilled the pillars and conditions determined by each religion. Every child is entitled to legal protection of their rights by providing a birth certificate as an identity, also makes it easier for children to a public service and get protection from violence and discrimination. As a result of the issuance of a birth certificate of a child from an unregistered marriage, the child will have a birth certificate with only the mother's name listed, resulting in the recognition of nasab or lineage, inheritance rights, maintenance and living expenses, even affection and parental responsibility for the growth and development of the child. The government should make a definite rule regarding the requirements that must be attached in terms of recording the birth certificate of a child born from an unregistered marriage. Legal certainty for the issuance of birth certificates of children from unregistered marriages should be synchronized in accordance with the relevant laws and regulations.